Gauging the Impact of Payment System Innovations on Financial Intermediation: Novel Empirical Evidence from Indonesia. (December 2019) - Lubis, Alexander; Alexiou, Constantinos; Nellis, Joseph G.
In this article, the relationship between innovations in the payment systems and financial intermediation is explored. By focusing on excess reserves and currency demand we provide evidence on the extant transmission mechanism. In this direction, a generalised method of moments (GMM) and vector error correction model (VECM) techniques are applied to a data set collated for Indonesia. We find that financial intermediation is affected by currency demand while we observe a limited role of excess reserves affecting financial intermediation. Credit card payments are found to have a statistically significant effect on currency demand, whereas debit card payments only influence financial intermediation in the long run. In addition, the real-time gross settlement (RTGS) exerts an upward pressure on excess reserves. The findings are of great importance as they provide support to policies that favour payment migration to an electronic platform, particularly that of card-based payment systems. JEL Classification: E42, E58, N25, G21